Migration of a Percutaneous Endoscopic Gastrojejunostomy Tube into the Colon with Small Intestinal Telescoping - Shinya Taki; Takao Maekita; Mayumi Sakata; Kazuhiro Fukatsu; Yoshimasa Maeda; Mikitaka Iguchi; Hidefumi Ito; Masayuki Kitano (Korean Society of Gastrointestinal Endoscopy, 2019)
Continuous duodenal levodopa/carbidopa intestinal gel delivery by a gastrostomy infusion system improves control of Parkinson's disease. The overall complication rates of percutaneous endoscopic gastrojejunostomy were reported to be 41% and 59% for immediate and delayed adverse events, respectively. A 72-year-old woman underwent percutaneous endoscopic gastrojejunostomy using the delivery system noted above. Abdominal pain and vomiting occurred 3 months later. Esophagogastroduodenoscopy showed a longitudinal ulcer extending from the lower gastric body to the ileum end, with small intestinal telescoping. Colonoscopy showed a large bezoar of food residue that was attached around the tip of the tube, reaching the ascending colon, which may have acted as an anchor. Thus, the gastric antrum and small intestine were shortened with telescoping. This complication was resolved by crushing the bezoar with forceps during colonoscopy and can be prevented by consuming a fiber-free diet and periodic exchanges of the tube using esophagogastroduodenoscopy.